An approach to Peruvian Consular Law: new challenges in uncertain times - Gallardo Garrath, Martin (2022)
In this article, the author addresses the contemporary conception of Consular Law and how it is understood in the light of international legislation and the Peruvian legal system. At the same time, he describes the challenges that Peruvian consular institutions must face in the 21st century and especially in the post-COVID-19 era. To this end, the author begins by explaining the contemporary concept of Consular Law in accordance with international regulations and authoritative doctrine. Subsequently, he analyses Peruvian legislation and how it influences consular institutions and their actions. Finally, he focuses on explaining the main challenges that the executors of consular policy must face today.